2007
DOI: 10.1109/tbme.2007.894629
|View full text |Cite
|
Sign up to set email alerts
|

A Multichannel Semicircular Canal Neural Prosthesis Using Electrical Stimulation to Restore 3-D Vestibular Sensation

Abstract: Bilateral loss of vestibular sensation can be disabling. Those afflicted suffer illusory visual field movement during head movements, chronic disequilibrium and postural instability due to failure of vestibulo-ocular and vestibulo-spinal reflexes. A neural prosthesis that emulates the normal transduction of head rotation by semicircular canals could significantly improve quality of life for these patients. Like the 3 semicircular canals in a normal ear, such a device should at least transduce 3 orthogonal (or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
215
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 150 publications
(225 citation statements)
references
References 55 publications
8
215
1
1
Order By: Relevance
“…As described in detail in previous publications Chiang et al 2011;Della Santina et al 2007;Davidovics et al 2013), the mapping function was sigmoidal, smooth, and approximately linear for small deviations about the baseline pulse rate of 94 pps. The maximum pulse rate (e.g., during excitatory head rotations at 9300°/s) was 400 pps, and the minimum pulse rate (e.g., during inhibitory head rotations at 9300°/s) was 0 pps.…”
Section: Prosthetic Stimulation Paradigmmentioning
confidence: 75%
See 4 more Smart Citations
“…As described in detail in previous publications Chiang et al 2011;Della Santina et al 2007;Davidovics et al 2013), the mapping function was sigmoidal, smooth, and approximately linear for small deviations about the baseline pulse rate of 94 pps. The maximum pulse rate (e.g., during excitatory head rotations at 9300°/s) was 400 pps, and the minimum pulse rate (e.g., during inhibitory head rotations at 9300°/s) was 0 pps.…”
Section: Prosthetic Stimulation Paradigmmentioning
confidence: 75%
“…Previous experiments have shown that misalignment between the actual axis of head motion and the perceived axis (as indicated by the VOR axis) occurs during prosthetic electrical stimulation of ampullary nerves, probably due to current spread (Della Santina et al 2007;Lewis et al 2010;Fridman et al 2010;Hayden et al 2011). Here, we examined whether misalignment can be reduced through central adaptation via a directional plasticity mechanism similar to that which arises when normal animals are exposed to directionally altered visual scene movement coupled to head rotation.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations